Studi Eksegesis Yohanes 3:16 dan Implikasinya bagi Karya Keselamatan: Studi Eksegesis Yohanes 3:16 dan Implikasinya bagi Karya Keselamatan - Lase, Arie (Sekolah Tinggi Teologi Berita Hidup, 2025)
Abstract God's saving love is the most fundamental doctrine in the Christian faith. In the text of John 3:16 it explains that for God so loved the world, that He gave His only Son, that whoever believes in Him should not perish but have eternal life. This study explains this text so that believers realize that sinful humans obtain salvation or eternal life not because of human effort itself, or good deeds but solely because of God's grace. Thus, it is hoped that all believers can realize God's grace with gratitude and humility before God. Then called to proclaim to the world about God's saving grace in the Lord Jesus Christ.